2000
DOI: 10.1108/00070700010336517
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeat consumption on pleasantness, preference and intake

Abstract: The pleasantness of a food declines with consumption and this phenomenon has been demonstrated reliably in the short-term. To investigate long-term effects of repeat consumption on pleasantness, preference and intake, 21 volunteers consumed either a salty snack (french fries) or sweet snack (chocolate) every day for 15 days. Four dependent variables were measured: pleasantness ratings, ranked preference, frequency of consumption and ad libitum intake. Daily pleasantness of taste ratings decreased across the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 20 publications
8
63
1
Order By: Relevance
“…A recent repeat exposure study reported a decline in preference ratings with consumption of a sweet high-fat snack food (chocolate) for 15 days but no change with a salty high fat snack food (fries). 20 The peanuts used in this study were salty and high in fat which may have contributed to the observed stability of pleasantness ratings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent repeat exposure study reported a decline in preference ratings with consumption of a sweet high-fat snack food (chocolate) for 15 days but no change with a salty high fat snack food (fries). 20 The peanuts used in this study were salty and high in fat which may have contributed to the observed stability of pleasantness ratings.…”
Section: Discussionmentioning
confidence: 99%
“…19 -21 Repeated consumption of a salty, high-fat snack (fries) did not diminish pleasantness ratings while a decline was noted after regular exposure to a sweet high fat snack (chocolate). 20 Thus, regular peanut consumption may lead to decreased acceptance due to monotony or, alternatively, hedonics may be preserved due to high initial acceptance or sensory profile. This study examined the effects of chronic peanut consumption on hedonic ratings for peanuts and other snack foods varying in their predominant taste qualities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all other studies, exposure to other sweet foods were simultaneously permitted in all groups and conditions. Measured outcomes of relevance to our research question were: liking or pleasantness of sweet foods (other than those in the exposure manipulation) (28,30,32), appetite for sweet foods (28), explicit wanting or demanding sweet foods (19,28), implicit wanting sweet foods (29), preferences for sweet foods (28,(30)(31)(32) or sweetness concentrations (20), and intake of sweet foods (19,(28)(29)(30).…”
Section: Included Studiesmentioning
confidence: 99%
“…Methodologic details of these studies are given in Table 3. 30). In the between-subjects studies, children and adults were randomly assigned to 8 d exposure to ≤200 mL sweetened beverages (20) (32).…”
Section: Included Studiesmentioning
confidence: 99%